Association between Clinical Symptoms and Histological Features of Molars with Acute Pulpitis - Dastpak, Mahsa; Ghoddusi, Jamileh; Jafarian, Amir Hossein; Sarmad, Majid (Iranian Endodontic Journal, 2023)
Introduction: Diagnosis of dental pulp status on the basis of clinical signs in many cases helps clinicians to better resolve patient problems. Various studies have shown no correlation between clinical and histologic findings. The aim of the present study was to evaluate the associations between clinical findings and histological features in extracted decayed teeth with acute pulpitis. Materials and Methods: One hundred permanent cavitated human teeth with mature apices and pulpitis, which were extracted for reasons not related to the present study, were evaluated. Demographic, clinical, and radiographic data were collected using pre-designed questionnaires. After tooth extraction, 5 micron-thick slices were prepared for microscopic assessment. General pathologist evaluated reactions to stimuli in all areas of the pulp tissue under a light microscope. When present, inflammation was classified according to the type and spread of cell detected and other histological findings, such as abscess formation, pulp stones, and pulpal fibrosis, were also recorded. Results: We found significant associations between pain characteristics, such as pain type and duration, and histological status. Acute inflammation, severe chronic inflammation, and liquefactive necrosis increased with pain severity. Various histological sections showed the absence of pulpal inflammation. Conclusions: We found a good agreement of patients’ pain histories and pain characteristics with histological pulp status. Thus, the use of specified CHARTs and SCALEs that help patients provide the most accurate responses to questions about pain would aid the diagnosis of pulp status. In cases with an accurate pulpal diagnosis, the clinicians can manage pulpal protection when it is possible.